FACULTY PERSPECTIVES ON PRISME INTEGRATION IN UNDERGRADUATE BDS CURRICULUM (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Undergraduate dental education is increasingly shifting toward integrated, competency-based curricula that prepare graduates for clinical, ethical, research-oriented, digital, community-responsive, and practice-management roles. PRISME integration, comprising Professionalism, Research, Informatics, Social accountability, Management and entrepreneurship, and Evidence-based dentistry, may provide a structured framework for strengthening the undergraduate BDS curriculum. However, successful implementation depends largely on faculty readiness, institutional capacity, and assessment alignment. Objective: To assess faculty perspectives, readiness, perceived barriers, and implementation preferences regarding PRISME integration in the undergraduate BDS curriculum. Methods: A descriptive cross-sectional study was conducted at de’Montmorency College of Dentistry Lahore, Pakistan from July to December 2025. A total of 90 faculty members involved in undergraduate BDS teaching were included through non-probability consecutive sampling. Data were collected using a structured questionnaire covering demographic characteristics, perceived importance and feasibility of PRISME domains, current preparedness, barriers, and implementation recommendations. Data were analyzed using IBM SPSS Statistics version 25.0. Descriptive statistics were reported, and associations were assessed using chi-square/Fisher’s exact test, independent-sample t-test, and multivariable logistic regression where appropriate. Results: The mean age of faculty members was 39.7 ± 8.6 years, and the mean teaching experience was 10.4 ± 6.7 years. Male faculty accounted for 52.2%, while 47.8% were female. Overall, 85.6% of faculty showed either strong or moderate readiness for PRISME implementation. Professionalism and evidence-based dentistry were rated as the highest-priority domains, whereas management and entrepreneurship showed comparatively lower feasibility and preparedness scores. Most faculty supported phased implementation (72.2%), spiral integration across all BDS years (82.2%), assessment-linked teaching (76.7%), and faculty-development workshops before implementation (92.2%). Major barriers included insufficient faculty training (84.4%), overloaded curriculum (78.9%), lack of protected teaching time (75.6%), limited standardized guidelines (71.1%), and difficulty in assessment design (65.6%). Prior exposure to PRISME or integrated curriculum and prior curriculum-development training were independent predictors of high readiness. Conclusion: Faculty members demonstrated favorable perceptions and substantial readiness for PRISME integration in the undergraduate BDS curriculum. However, successful implementation requires phased planning, faculty development, year-wise curriculum mapping, protected teaching time, digital support, and standardized